The Effect of Using Who Is It Game On Students’ Speaking Ability - Rima Aulia Fayi; Enni Maisaroh (Universitas Muhammadiyah Enrekang, 2025)
This research investigated the impact of the Who Is It game on enhancing students' speaking skills at MTS Swasta Darul Ulum Budi Agung Medan. It was driven by the challenges students faced in acquiring grammar, vocabulary, and fluency in English communication. The study explored whether incorporating game-based learning could create a more engaging classroom dynamic and boost students' self-assurance and enthusiasm for speaking. Employing a quantitative methodology with a quasi-experimental framework, the study involved 66 participants split into two groups: 30 in the experimental group, who received instruction via the Who Is It game, and 36 in the control group, who followed traditional teaching approaches. Data collection relied on pre-test and post-test evaluations of speaking performance, assessed using Brown’s (2004) rubric. Statistical analysis included tests for normality, homogeneity, and an independent samples t-test. The outcomes showed that the experimental group attained a higher average post-test score (84.00) compared to the control group (75.53), with a significance level of Sig. (0.000) below 0.05, demonstrating a notable advancement in speaking abilities through the game. These results imply that the game successfully improves speaking proficiency by encouraging active participation, alleviating speaking apprehension, and establishing a supportive and pleasurable learning setting. Consequently, educators are advised to adopt interactive games as a viable method to strengthen communicative skills in English as a foreign language classrooms.